Clinical Pharmacokinetics, Pharmacodynamics, Safety and Efficacy of Liposomal Amphotericin B. (2nd May 2019) - Groll, Andreas H; Rijnders, Bart J A; Walsh, Thomas J; Adler-Moore, Jill; Lewis, Russell E; Brüggemann, Roger J M
Abstract: Since its introduction in the 1990s, liposomal amphotericin B (LAmB) continues to be an important agent for the treatment of invasive fungal diseases caused by a wide variety of yeasts and molds. This liposomal formulation was developed to improve the tolerability of intravenous amphotericin B, while optimizing its clinical efficacy. Since then, numerous clinical studies have been conducted, collecting a comprehensive body of evidence on its efficacy, safety, and tolerability in the preclinical and clinical setting. Nevertheless, insights into the pharmacokinetics and pharmacodynamics of LAmB continue to evolve and can be utilized to develop strategies that optimize efficacy while maintaining the compound's safety. In this article, we review the clinical pharmacokinetics, pharmacodynamics, safety, and efficacy of LAmB in a wide variety of patient populations and in different indications, and provide an assessment of areas with a need for further clinical research.